Efficacy and safety of fire-needle in the treatment of gouty arthritis: A protocol for systematic review and meta analysis. Issue 30 (24th July 2020) - Sun, Jiya; Fan, Yihua; Yang, Zhihua; Jin, Rui; Xin, Ping; Cai, Xuemeng; Li, Xinju; Wang, Shenjun
Abstract: Background: Fire needle therapy is an ancient external treatment method of traditional Chinese medicine. This therapy is simple to operate and has fewer side effects. Gouty arthritis (GA) is common disease that is often characterized by high excruciating pain on joint. Evidence from clinical studies show that fire needle exerts therapeutic effects on gout arthritis, but no evidence-based medicine is available. This study aimed to evaluate the efficacy and safety of fire acupuncture in the treatment of gout arthritis. Methods: Randomized controlled trials of fire needle in the treatment of GA published until May 2020 will be searched in the English databases (PubMed, EMBASE, Web of Science, the Cochrane Library) and Chinese databases (China National Knowledge Infrastructure, the Chongqing VIP Chinese Science and Technology Periodical Database, Wanfang database, and China Biomedical Literature Database). Additional search will be performed on Google academy and Baidu Academy. Data will be extracted from the studies by 2 reviewers working independently. Subsequently, quality assessment and a meta-analysis will be carried out for the studies using RevMan 5.3. Results: The efficacy and safety of fire needle in the treatment of GA will be evaluated based on overall effective rate, visual analog scale, blood uric acid, C-reactive protein, joint swelling and pain score, adverse reaction rate, and other clinical outcomes. Conclusions: The proposed systematic review and meta-analysis are expected to provide reliable evidence for the clinical benefits of fire-needle therapy in GA.